Macro and micro-elements concentrations in Calligonum comosum wild grazing plant through its growth period - Mohamed I. Alzarah (Elsevier, 2021)
In this study, the change in the content of the macro and micro elements in the growing wild grazing plant of Calligonum comosum was tracked at the Research and Training Station of King Faisal University in Al-Hassa Governorate, Kingdom of Saudi Arabia. Mineral elements were estimated in aerial parts (plant as a whole, leaves and stem) from January-April 2020. The results showed that the concentration of nitrogen, phosphorus and potassium in the plant as a whole plant > leaves > roots, while the concentrations of calcium, magnesium, manganese, zinc and copper elements in the leaves was higher than other parts whereas the concentrations of these elements of whole plant were higher than the concentrations in roots. The results showed that the plant contents of nitrogen, potassium and zinc were the highest in March, while the concentrations of phosphorus, calcium, iron and copper were in February. The concentrations of magnesium, manganese and copper was the highest in January and April respectively. The values ​​of nitrogen, phosphorous, potassium, calcium, magnesium, iron, manganese, zinc and copper ranged from 11.1 to 18.4 g kg−1, 4.17–2.33 g kg−1, 13.73–18.97 g kg−1, 24.50–28.90 g kg−1, 10.40–12.30 gkg−1, 1500–1677 mg kg−1, 45.45–49.29 mg kg−1, 70.70–177.23 mg kg−1, 16.78–73.46 mg kg−1, respectively. Furthermore, the results exhibited that the lowest values of the elements appeared in the plant roots in April. As well as, the distribution of the elements followed the normal life curve from January to April. Besides that, the evaluated elements satisfy the needs of the grazing animals' life in which this type of plant grows.